The Effects of Different Insufflation Pressures on Liver Functions Assessed with LiMON on Patients Undergoing Laparoscopic Cholecystectomy. (24th April 2012) - Eryılmaz, H. Barıs; Memiş, Dilek; Sezer, Atakan; Inal, Mehmet Turan
Abstract : Purpose . Laparoscopic cholecystectomy has been accepted as an alternative to laparotomy, but there is still controversy regarding the effects of pneumoperitoneum on splanchnic and hepatic perfusion. We assessed the effects of different insufflation pressures on liver functions by using indocyanine green elimination tests (ICG-PDR). Methods . We analyzed 43 patients who were scheduled for laparoscopic cholecystectomy. The patients were randomly allocated to two groups. In Group I, the operation was performed using 10 mmHg pressure pneumoperitoneum. In Group II, 14 mmHg pressure pneumoperitoneum was used. The ICG-PDR measurements were made after induction (ICG-PDR 1) and after the end of the operation (ICG-PDR 2). Serum aspartate aminotransferase (AST), alanine aminotransferase (ALT), and total bilirubin levels were all recorded preoperatively, 1 hour, and postoperative 24 hours after surgery. Results . The ICG-PDR 1 values for Groups I and II were as follows: 26.78 ± 4.2 % per min versus 26.01 ± 2.4 % per min (P > 0.05 ). ICG-PDR 2 values were found to be 25.63 ± 2.1 % per min in Group I versus 19.06 ± 2.2 % per min in Group II (P < 0.05 ). There was a statistically significant decrease between baseline and postoperative ICG-PDR values in Group II compared to Group I (P < 0.05 ). Statistically, there was an increase between baseline and postoperative 1st-hour serum AST and ALT level in Group II (P < 0.05 ) compared to Group I. No statistical differences were detected on postoperative 24st-hour serum AST and ALT levels and all the time bilirubin between groups (P > 0.05 ). Conclusion . In conclusion, the results show that 14 mmHg pressure pneumoperitoneum decreased the blood flow to the liver and increased postoperative 1st-hour serum AST and ALT levels. We think that 10 mmHg pressure pneumoperitoneum is superior to 14 mmHg pressure pneumoperitoneum in laparoscopic cholecystectomy.